Amélia não! Amely, a boneca inflável: uma análise retórica da tirinha cômica de Pryscila Vieira - Silva, Helena Madeira Caldeira (2016)
This research proposes to analyze five comic strips of the character Amely, created by the cartoonist Pryscila Vieira and published in the book Amely, uma mulher de verdade, in 2015. They were selected considering those that most express the identity of the title character and the mood that characterizes it. From the 150 works published by the author, in the book, we select those that bring Amely as a thinking woman (and acting) and not submissive to the desires of the companion. The choice also features an Amely who discusses the relationship with the partner and charges him. The objective is to understand the rhetorical structure of these strips, verifying how they achieve the adhesion of readers and promote laughter. For this, we will demonstrate how Vieira uses intertextuality and rhetorical figures as argumentative strategies for comedy. Moreover, in the case of a verbo-visual text, we will also verify how other expressive features of the comic language are manifested in the strips, contributing to the effectiveness of humor. The analysis is based on the notions derived from the Textual Linguistics of Cavalcante (2014), Koch (2012) and Marcuschi (2007). In relation to the rhetoric, the studies of Aristóteles (2000, 2005), Fiorin (2012, 2014, 2015), Meyer (2007), Reboul (2004) and Perelman and Olbrechts-Tyteca (2014) will be evoked. To support the study of the language of comics, we present the concepts of Ramos (2011; 2012), Eisner (1999; 2013), Garcia (2012) and Campos (2015). This work raises important discussions about feminine discourse, but also promotes rhetorical studies, applying them to verbal-visual texts.